Correlates and predictors of job satisfaction among elementary school teachers in five Dominical schools in Metro Manila - Seguban, Ma. Esperanza H., OP (Animo Repository, 1989)
Unionism and strikes are said to be the end result of job dissatisfaction which may be traceable to the administrators’ managerial leadership. Although there are some indications that personal characteristics of attributes like age, sex, educational attainment, length of service and socio-economic status may have a bearing on job satisfaction, still it has to be proven. It is in this light that the researchers has embarked on this study.